ANALISIS BELANJA NEGARA, SUKU BUNGA RIIL, INDEKS PRODUKSI INDUSTRI, DAN PMTB TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Nur Indah Sar Sari; Purwiyanta (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2026)
Economic growth is an indicator of the success of a country’s development, which is influenced by macroeconomic policies, the real sector, and investment. However, the dynamics of Indonesia’s macroeconomic policies, real sector performance, and investment have shown challenges in influencing economic growth. In this study, macroeconomic policy is represented by fiscal policy through government expenditure and monetary policy through the real interest rate, while the real sector is proxied by the industrial production index, and investment is measured by gross fixed capital formation. This study to analyze the effects of government expenditure, real interest rate, industrial production index, and gross fixed capital formation on Indonesia’s economic growth during the period 2005Q1–2024Q4 using the Autoregressive Distributed Lag (ARDL) approach. The empirical results indicate that in the short run, government expenditure has a positive effect, the industrial production index has a negative effect, while the real interest rate and gross fixed capital formation have no significant effect on economic growth. In the long run, the industrial production index has a positive effect, whereas government expenditure, real interest rate, and gross fixed capital formation have negative effects. These findings imply that Indonesia’s economic growth is primarily driven by government